2022
DOI: 10.1039/d2cp02351b
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Schottky barrier of MXenes/2D SiC contacts via functional groups and biaxial strain: a first-principles study

Abstract: 2D MXene Ti3C2T2 (T=F, O, OH) are employed to serve as electrode for 2D SiC through van der Waals interaction. The Schottky barrier height of contacts can be tuned by changing the functional T group of Ti3C2T2 and applying biaxial strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…By comparison, E g values of 2D SiC (C Si )/CaF 2 and 2D SiC (C i )/CaF 2 are further reduced by 0.03 and 0.15 eV, respectively. The difference in the reduction of E g values may be ascribed to the stronger interfacial interaction at the 2D SiC (C i )/CaF 2 interface than that at the 2D SiC (C Si )/ CaF 2 interface, 50 which can be confirmed by charge-density difference curves, as shown in Figure 12a,b. As can be seen, for 2D SiC (C Si )/CaF 2 , the charges are depleted near the CaF 2 side and accumulated on the 2D SiC side.…”
Section: Effects Of Cmentioning
confidence: 70%
“…By comparison, E g values of 2D SiC (C Si )/CaF 2 and 2D SiC (C i )/CaF 2 are further reduced by 0.03 and 0.15 eV, respectively. The difference in the reduction of E g values may be ascribed to the stronger interfacial interaction at the 2D SiC (C i )/CaF 2 interface than that at the 2D SiC (C Si )/ CaF 2 interface, 50 which can be confirmed by charge-density difference curves, as shown in Figure 12a,b. As can be seen, for 2D SiC (C Si )/CaF 2 , the charges are depleted near the CaF 2 side and accumulated on the 2D SiC side.…”
Section: Effects Of Cmentioning
confidence: 70%
“…where m and ℏ are the mass of free and reduced Planck's constant. 55 The tunneling-specific resistivity (ρ t ) can be used to measure interfacial contact resistance, 23 which can be calculated by the Simon model 56 as follows…”
Section: Resultsmentioning
confidence: 99%
“…However, P TB values of all of the OH-MXene/MoSi 2 N 4 VHTs are higher than 50%, especially those of Nb 2 N­(OH) 2 /MoSi 2 N 4 , Ta 2 N­(OH) 2 /MoSi 2 N 4 , and Ta 3 N­(OH) 2 /MoSi 2 N 4 VHTs up to 100%, indicating the high carrier injection efficiency, which is caused by the absence of the tunneling barrier. Although the O- and OH-MXenes exhibit OhC (or quasi-OhC) to MoSi 2 N 4 , the lower P TB of O-MXene/MoSi 2 N 4 VHTs results in higher contact resistances …”
Section: Results and Discussionmentioning
confidence: 99%
“…In the MAX family, Ti 3 AlC 2 stand out by its unique set of properties of both metals and ceramics, which have been applied in different applications in nuclear energy material, catalysis, battery and CO 2 conversion reactions [27–30] . MXenes are an emerging of two‐dimensional (2‐D) materials fabricated by selectively removing the metal layer from the MAX phases [31–33] . As a class of 2‐D materials with splendid work function, the MXenes have shown great potential in a host of applications, including solar cells, hydrogen storage, supercapacitors and flexible sensors due to their excellent chemical stability, intriguing structural property, high electrical conductivity and tunable physical/chemical properties [34–37] .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] MXenes are an emerging of two-dimensional (2-D) materials fabricated by selectively removing the metal layer from the MAX phases. [31][32][33] As a class of 2-D materials with splendid work function, the MXenes have shown great potential in a host of applications, including solar cells, hydrogen storage, supercapacitors and flexible sensors due to their excellent chemical stability, intriguing structural property, high electrical conductivity and tunable physical/chemical properties. [34][35][36][37] However, no research works were reported on investigating Ti 3 AlC 2 nanomaterials dual-analysis in the application of PTMs proteomics.…”
Section: Introductionmentioning
confidence: 99%